A múltipla Cecília (Polifonia, 2002)
ABSTRACT: We are members of a group which researches Cecília Meireles poetry. Our aim in this paper is to offer a broad comprehension of the writer's world view, looking for relations between the poetic and the other dimensions. We are going to present three different portraits: 1) Cecilia as a Literature scholar; 2) Cecilia as a folklorist; 3) Cecilia as a journalist writing about education.